6 - Privatisation de la sécurité et gouvernance démocratique au Cameroun - Désiré Manirakiza (African Sociological Review, 2017)
This article focuses on the Cameroonian State and the opening up of the field of security to private actors, an indicator of a progressive civilization of political mores, On the one hand, the article shows that the decompartmentalization of the security sector is an axis from which to analyze the processes as diverse as those relating to the extension of the spheres of civil liberties, security pluralism and Decriminalization of the Other different from the State. On the other hand, it highlights the complementary relationships that exist between private security agents and police forces, which are in line with governance as applied in modern societies.